2008
DOI: 10.1158/1535-7163.mct-08-0095
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of centromere dynamics by eribulin (E7389) during mitotic metaphase

Abstract: Eribulin (E7389), a synthetic analogue of halichondrin B in phase III clinical trials for breast cancer, binds to tubulin and microtubules. At low concentrations, it suppresses the growth phase of microtubule dynamic instability in interphase cells, arrests mitosis, and induces apoptosis, suggesting that suppression of spindle microtubule dynamics induces mitotic arrest. To further test this hypothesis, we measured the effects of eribulin on dynamics of centromeres and their attached kinetochore microtubules b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(137 citation statements)
references
References 19 publications
6
127
0
4
Order By: Relevance
“…Studies by Alday and Correia (26) showed that ER-076349, but not eribulin, enhances tubulin self-association into oligomers by binding at or near interdimer interfaces, suggesting that ER-076349 can associate with existing oligomers, including microtubule sides. This would dramatically increase the number of intracellular binding sites for ER-076349 relative to eribulin, and explain both our findings and those of Okouneva and colleagues (14) ]ER-076349. Thus, although eribulin would bind to lower numbers of intracellular sites than ER-076349, its overall binding affinity would be greater, resulting in slower off-rates and more persistent postwashout retention.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Studies by Alday and Correia (26) showed that ER-076349, but not eribulin, enhances tubulin self-association into oligomers by binding at or near interdimer interfaces, suggesting that ER-076349 can associate with existing oligomers, including microtubule sides. This would dramatically increase the number of intracellular binding sites for ER-076349 relative to eribulin, and explain both our findings and those of Okouneva and colleagues (14) ]ER-076349. Thus, although eribulin would bind to lower numbers of intracellular sites than ER-076349, its overall binding affinity would be greater, resulting in slower off-rates and more persistent postwashout retention.…”
Section: Discussionsupporting
confidence: 85%
“…Eribulin works via apoptosis-inducing, microtubule-targeting antimitotic mechanisms (10,12) involving inhibition of microtubule dynamics by mechanisms distinct from most other tubulin-targeting agents (13)(14)(15). Eribulin's mechanistic novelty is noteworthy when considering the original mechanistic studies on HB, which showed it to have a spectrum of biochemical effects on tubulin that was distinct from other tubulin-targeted drugs (16).…”
Section: Introductionmentioning
confidence: 99%
“…There are also a few remarkable drugs from marine sources, such as the recently approved anticancer drug eribulin, a synthetic analog of halichondrin B isolated from the sponge Halichondria okadai [4]. In the microbial area the main sources have been terrestrial actinomycetes and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…4H, P < 0.001). 14 C]-docetaxel (-}-) in MCF7 cells over time was determined as described (36). Docetaxel was taken up relatively slowly, attaining an intracellular concentration of 25 mmol/L after 10 hours, and remaining at approximately that level for the next 20 hours (Fig.…”
Section: Both Drugs Suppress Dynamic Instability Of Microtubules In Lmentioning
confidence: 99%